Gout Therapy With Reduced Kidney Function - Fayzullaevna, Mirzaeva Gulchehra; Otakhanovich, Jabbarov Ozimbay; Tokhirovna, Buvamukhamedova Nasiba; Mamatovich, Rakhmatov Avaz; Bakhadirovich, Jumanazarov Sultanbay (Central Asian Journal of Medical and Natural Science, 2022)
Gout is often combined with kidney disease. The pathology itself and concomitant hyperuricemia are considered as independent nephrotoxic factors. Urate-reducing therapy of gout can level the pathogenic effect of uric acid, preventing the development and progression of chronic kidney disease. However, in patients with reduced kidney function, its choice should be more careful. It is important to select not only the optimal urate-reducing drug, but also its dosing regimen. In this population, it is also difficult to set treatment goals and methods to evaluate its effectiveness. Xanthine oxidase inhibitors appear to be the most promising in the presence of renal pathology.